In vitro estimation and characterization of drug-plasma protein interaction - Obradović, Darija; Vujić, Zorica (Archives of Pharmacy, 2022)
The characterization of drug-protein plasma interactions is a routinely performed part of drug discovery process. The unbound concentration of the drug depends on the binding affinity to plasma proteins, which consequently affects its therapeutic effect, absorption, distribution, metabolism and excretion. The most important plasma proteins are human serum albumin (HSA), lipoproteins and alpha-1 acid glycoproteins (AGP). The liquid chromatography can be successfully used for in vitro estimation of plasma protein binding affinity using HSA or AGP modified silica gel as a stationary phase. The interaction with HSA has been tested for a wide range of 33 pharmacologically active compounds including dipeptidyl peptidase IV inhibitors, angiotensin-converting enzyme inhibitors, β-blockers, calcium channel blockers and serotonin/dopamine receptor ligands under reversed-phase conditions. The drug-HSA interaction was interpreted by using the retention modeling, and by selecting the most significant structural characteristics that have an influence on the retention mechanism. The small structural differences, which are reflected in different lipophilicity and polarity, affect the drug-HSA interaction. The retention of the compounds was successfully defined by using the quadratic equation. The isocratic (logk(14%)) and extrapolated factors (b0(LSS)) showed a high correlation with the experimentally available data, and in silico estimated affinity for HSA. The structural properties and charged parts of the molecule surface have been found to significantly affect the HSA mechanism. The obtained results can be successfully applied in further optimization of the structural characteristics of the newly synthesized compounds in order to achieve the desired therapeutic and pharmacokinetic effect.